Translation Based on Ogden and Richard’s Semantic Triangle Theory - Rizka Aprilya; Afriyanti Simamora; Vira Budiarti; Yona Dwi Tirta Syafitri (Universitas Muhammadiyah Barru, 2020)
This paper aims to analyze the process of translators in translation based on semantic triangle theory in Indonesia. It parts of its intentions to provide some references for related researchers which focus on the theory of reference triangle as it is one of the important theories in Semantic field. The exploration of this study sees the reference triangle is a theory well known by the scholars for decades able to explain how words convey meaning. This study addressed that “the how” of this theory workings are like words that suggest ideas in the listener's mind. Which explains how the idea is connected to real-world objects. The triangle reference somehow continues to be used as a model for semiotic relationships into the 21st century, this theory also has several potential deficiencies that could limit its application. Which means that this theory still applicable to be used as a current meaning-framework in translation based semantic.